Effects of Pilates and Vitamin E on Symptoms of Premenstrual Syndrome - Fatemeh Omidali (Golestan University of Medical Sciences, 2016)
Background: Premenstrual syndrome (PMS) is a set of physical, emotional and behavioural changes that appear in the late luteal phase of the menstrual cycle. Given the high prevalence of this syndrome among women, this study aimed to evaluate the effects of Pilates workouts and vitamin E consumption on symptoms of PMS. Methods: In this semi-experimental study, 40 non-athletic female students with diagnosed moderate to severe PMS were selected from the University of Ayatollah Boroujerdi. The students were randomly divided into four groups of "Pilates, Pilates along with vitamin E, vitamin E and controls". Pilates workouts were performed for 4 weeks, three session a week with consumption of one vitamin E tablet a day. Subjects were analysed using the PMS symptoms screening questionnaire before and after the intervention. Analysis of variance and t-test were performed to compare the obtained data at significance level of P<0.05.  Results: There was no significant difference between the four groups before the intervention. In the Pilates group and vitamin E group, the intensity of mood symptoms (P=0.0001) and physical symptoms (P=0.002), and the impact of these symptoms on individuals’ lives (P=0.0001) reduced significantly in comparison with data before the intervention and the control group. Conclusion: Pilates along with vitamin E consumption improves the symptoms of PMS among the participants of this study.